2020
DOI: 10.1111/ejn.14877
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and oxidative stress variations in a murine model of Alzheimer’s disease progression

Abstract: Alzheimer's disease (AD), the most common cause of dementia, is defined by progressive and irreversible neurodegeneration of the central nervous system that eventually leads to the gradual decline of cognitive function (Czech, Tremp, & Pradier, 2000; Oddo et al., 2003). The main feature of this disease is the deposition of amyloid-β

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…TL difference between 3xTg and WT mice was less evident in the study of Martínez‐González et al. ( 2020 ) and the significance was only achieved at the age of 13 months. In contrast, we found that TL difference between APP/PS1 and WT mice is extensive and depended on tissue type and age.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…TL difference between 3xTg and WT mice was less evident in the study of Martínez‐González et al. ( 2020 ) and the significance was only achieved at the age of 13 months. In contrast, we found that TL difference between APP/PS1 and WT mice is extensive and depended on tissue type and age.…”
Section: Discussionmentioning
confidence: 77%
“…In line with this study, we found an age-related decrease of TL in all six examined tissues (prefrontal cortex, pituitary gland, hippocampus, cerebellum, colon, and skin). TL difference between 3xTg and WT mice was less evident in the study of Martínez-González et al (2020) and the significance was only achieved at the age of 13 months. In contrast, we found that TL difference between APP/PS1 and WT mice is extensive and depended on tissue type and age.…”
Section: Accelerated Tl Attrition and Micronucleation Are Dominant Fe...mentioning
confidence: 84%
See 1 more Smart Citation
“…One of the most well researched epigenetic processes, DNA methylation modifies chromatin structure without changing nucleotide base sequences. Particularly in the human brain and blood ( García-Campayo et al, 2018 ), DNA methylation is crucial for controlling the expression of genes ( Martínez-González et al, 2020 ). Long-term MT can methylate genes including FKBP5 ( Bishop et al, 2018 ), SCL6A4 ( Stoffel et al, 2019 ), NR4A2 ( García-Campayo et al, 2018 ), and CLU ( Huang et al, 2016 ), influencing the proteins encoded by these genes, controlling the dynamic process of methylation and demethylation, and enhancing the organism’s benefit from the epigenetic process.…”
Section: Molecular Mechanism Of Mtmentioning
confidence: 99%
“…Despite evidence of early cellular and metabolic dysregulation and resilience to neuropathology, 8,12 very little is known about alterations in cellular chromosomal ribonucleoproteins, telomeres, in prodromal AD. In this regard, mounting evidence suggests that telomeres and telomere maintenance proteins, which modulate neuronal responses to both oxidative stress and DNA damage, 15‐18 are novel therapeutic targets 17,19 and biomarkers for AD 20,21 . The corticocortical projection neurons of the PreC have some of the highest metabolic demand in the cortex 22 suggesting that these neurons would be selectively vulnerable to telomeric dysregulation.…”
Section: Introductionmentioning
confidence: 99%